Foundations of Probabilistic Programming - Barthe, Gilles; Katoen, Joost-Pieter; Silva, Alexandra (Mathematical Sciences and Information Technology, 2021)
This book provides an overview of the theoretical underpinnings of modern probabilistic programming and presents applications in e.g., machine learning, security, and approximate computing. Comprehensive survey chapters make the material accessible to graduate students and non-experts. This title is also available as Open Access on Cambridge Core.